PENGARUH MODEL PEMBELAJARAN RADEC TERHADAP PENINGKATAN KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK DI SMAN 5 SAROLANGUN - Juniati, Elisa; Sukarno; Zainal Hartoyo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to analyze the effect of the RADEC learning model (Read, Answer, Discuss, Explain, Create) on improving students’ critical thinking skills in static fluid material at SMAN 5 Sarolangun. A quasi-experimental method with a nonequivalent control group design was employed. The subjects consisted of an experimental class taught using the RADEC model and a control class taught using conventional learning. The instruments included an essay test of critical thinking skills based on Ennis’ indicators, observation sheets, and a student response questionnaire. Data were analyzed using the Mann–Whitney U test, N-Gain analysis, and effect size analysis. The results indicated that students in the experimental class achieved higher critical thinking skills than those in the control class. The N-Gain value of the experimental class was in the moderate category and higher than that of the control class, with an effect size of 0.82, indicating a large effect. In addition, students’ responses to the RADEC learning model were positive, with an average score of 73.96 in the good category. It can be concluded that the RADEC learning model has a positive and significant effect on improving students’ critical thinking skills in static fluid material at SMAN 5 Sarolangun.